PRAGMATIC POTENTIAL OF THE NOMINATION OF THE SUBJECT-SOURCE OF FEAR (A MONSTROSITY) IN TEXTS OF HORROR DISCOURSE - Sazonova, Yaroslava (Verbum, 2018)
The research is aimed at studying the pragmatic potential of nominations of the subject-source of fear (a monstrosity, in particular) in texts of horror discourse in English and Ukrainian. The idea is that the expression of the communicative sense “fear” in a subjectively created world according to an author’s intention is explicated in the nomination of the subject-source of fear (SSF). Generally, any SSF is a monster as far as its attributes and actions are harmful for the recipient of fear (SRF), its essence contradicts the SRF’s world creating norms. Psychologically, a SSF-monstrosity is a metaphor that gives ground to a trend in the horror discourse (J. Hartwell) and preconditions the modus of fear emphasis that lets the reader concentrate his empathy on the SRF, revealing his hidden fears. In psychology this state is called dysmorphophobia, or an obsessive fear of deformities (both own and others). Alogism of SSFs’ reference includes repellent appearance as the feature of external inconsistency with the norms of the SRF’s world: in this sense it borders on the notion of otherness that, revealed to its fullest, may be perceived as horrific. On the other hand, deformities viewed as the features of some other world creation relate to the notion of novelty, and may be understood as not fearful. Both sense variations mentioned above are present in texts of horror discourse and actualize such senses as “fear-disgust”, “fear of the unknown” and “fear of otherness”; their differentiation helps exclude from the analysis tautological notion “fear of fearful”.
Keywords: pragmatic potential; horror discourse; text; communicative sense; fear; subject-source of fear; monstrosity